The rhetoric of fiction - Booth, Wayne C. (The University of Chicago Press, 1961)
"Rhetoric is the author's term for the means by which the writer makes known his vision to the reader and persuades him of its validity; and he demonstrates convincingly that there is no essential difference between ostentatiously rhetorical novelists like Fielding and Dickens, and the admired masters of impersonality--Flaubert, James, Joyce...this is a major critical work which should be required reading for everyone concerned in the academic study of prose fiction." [Modern Language Review].